2011
DOI: 10.1038/nmat3159
|View full text |Cite
|
Sign up to set email alerts
|

Universal energy-level alignment of molecules on metal oxides

Abstract: Transition-metal oxides improve power conversion efficiencies in organic photovoltaics and are used as low-resistance contacts in organic light-emitting diodes and organic thin-film transistors. What makes metal oxides useful in these technologies is the fact that their chemical and electronic properties can be tuned to enable charge exchange with a wide variety of organic molecules. Although it is known that charge exchange relies on the alignment of donor and acceptor energy levels, the mechanism for level a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
528
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 886 publications
(562 citation statements)
references
References 30 publications
34
528
0
Order By: Relevance
“…Although OA-doped graphene has an enhanced work function of B5.1 eV, it is not sufficient for direct hole injection into host materials such as 4,4 0 -bis(carbazol-9-yl)biphenyl (CBP), which has a HOMO level of 6.1 eV. Here we use anode interface layers consisting of the transition metal oxide to further enhance the work function of the graphene anode, similar to their roles of modifying the work function of ITO electrodes in organic electronics [38][39][40][41][42][43] . Note that metal oxides do not grow as uniform films on graphene due to the lack of nucleation to initialize the film growth 44,45 .…”
Section: Resultsmentioning
confidence: 99%
“…Although OA-doped graphene has an enhanced work function of B5.1 eV, it is not sufficient for direct hole injection into host materials such as 4,4 0 -bis(carbazol-9-yl)biphenyl (CBP), which has a HOMO level of 6.1 eV. Here we use anode interface layers consisting of the transition metal oxide to further enhance the work function of the graphene anode, similar to their roles of modifying the work function of ITO electrodes in organic electronics [38][39][40][41][42][43] . Note that metal oxides do not grow as uniform films on graphene due to the lack of nucleation to initialize the film growth 44,45 .…”
Section: Resultsmentioning
confidence: 99%
“…43,44 Here, we use a Kelvin Probe system to investigate the work function of various Csintercalation mole ratios of MoO x and V 2 O x . The MoO x and V 2 O x films formed on ITO/glass substrates exhibit work functions of 5.30 eV and 5.42 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…10), it is suggested that Ni incorporates into the CoOx lattice as opposed to forming a composite structure. Considering the work functions of monoclinic BiVO4 (5.27 eV) 54 and Co3O4 (6.1 eV) 63 , the interface band diagram for the n-type BiVO4/CoOx heterojunction is shown schematically in However, under the conditions used to evaluate ηcs and ηci (presence of a hole scavenger SO3 2-), the photo generated surface holes are consumed very rapidly. In this case, the enhanced charge transfer enabled by the larger band bending has only a small effect, as can be seen in Figures 9a and S5.…”
Section: Doping Of Ni Ions Inside Coox Layermentioning
confidence: 99%